2017
DOI: 10.1098/rspb.2016.2323
|View full text |Cite
|
Sign up to set email alerts
|

Non-glandular trichomes ofSolanum carolinensedeter feeding byManduca sextacaterpillars and cause damage to the gut peritrophic matrix

Abstract: Plant trichomes constitute a first line of defence against insect herbivores. The pre- and post-ingestive defensive functions of glandular trichomes are well documented and include direct toxicity, adhesion, antinutrition and defence gene induction. By contrast, the defensive functions of non-glandular trichomes are less well characterized, although these structures are thought to serve as physical barriers that impede herbivore feeding and movement. We experimentally varied the density of stellate non-glandul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 46 publications
9
108
0
2
Order By: Relevance
“…However, we found that non-glandular trichomes had little effect on the initiation of feeding in third-instar caterpillars. This result provides context for our previous report that third-instar caterpillars, while not deterred from initiating feeding, are detrimentally affected by non-glandular trichomes, which damage the peritrophic matrix [3]. Szyndler et al .…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…However, we found that non-glandular trichomes had little effect on the initiation of feeding in third-instar caterpillars. This result provides context for our previous report that third-instar caterpillars, while not deterred from initiating feeding, are detrimentally affected by non-glandular trichomes, which damage the peritrophic matrix [3]. Szyndler et al .…”
Section: Discussionsupporting
confidence: 63%
“…For example, we previously documented that M. sexta feeding on older leaves of Solanum carolinense induced a higher density of stellate trichomes (branched non-glandular trichomes with spikes) on both surfaces of new leaves after 21 days [5]. In the same system, we also demonstrated that non-glandular stellate trichomes cause physical injury to caterpillars and impede the ability of early instar caterpillars to locate the epidermis and commence feeding [3]. For neonate caterpillars of species like M. sexta , any delay in initiating feeding could potentially prove fatal due to increased risk of desiccation, starvation, and/or predation [11].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations